Analysis of criteria for choosing drug treatment strategies in allergic rhinitis - Grzegorzewski, Damian; Sobczak, Marharyta; Tołkacz, Michał; Pawliczak, Rafał (Frontiers in Pharmacology, 2024)
Background Allergic rhinitis (AR) is the most common type of rhinitis, the treatment of which relies on relieving symptoms. Therefore, we aimed to assess the criteria that influence doctors’ decision-making in the process of drug selection for the treatment of allergic rhinitis based on quantitative, qualitative, and cost analyses. Methods We conducted a survey study with the participation of 300 allergologists. A self-developed questionnaire was presented during a computer-assisted telephone interview (CATI) according to standard procedures. The contingency table underwent statistical analysis using the chi-square test with Cramer’s V. Results were considered statistically significant at p < 0.05. Results Our analyses showed that doctors most often prescribe intranasal glucocorticoids and oral antihistamines to treat allergic rhinitis in patients of all ages. The most common factor that affects the decision-making related to AR treatment was the efficiency of the drug. We found a significant relationship between factors and the main workplace (X-squared = 122.81, df = 90, p-value = 0.0123, Cramer’s V = 0.1787216), as well as voivodeship of the main workplace (X-squared = 440.75, df = 270, p-value = 2.378e-10, Cramer’s V = 0.1954731). In our study, respondents claimed that patients are willing to pay 31–50 PLN (∼€7- €11) monthly for the treatment of mild and moderate forms of AR, while they were willing to pay 51–100 PLN (∼€11–€22) for treatment of the severe AR form. Conclusion Our study confirms that the management of AR should be focused on the patient. One of the most important factors in choosing a drug is its effectiveness. Moreover, an important factor in the effective treatment of AR is the financial issue; as shown in our analysis, AR treatment costs can be a significant burden, especially for less wealthy citizens in Poland.